Metameric failure assessment and reduction between RGB and laser phosphor projectors. Issue 4 (11th January 2022) - Ploumis, Stelios; Boitard, Ronan; Ballestad, Anders; Damberg, Gerwin; Nasiopoulos, Panos
Abstract: Metameric failure is commonly observed when different types of displays reproduce the same color, as it is defined by a colorimetry system, but the outputs do not match visually. Metameric failure is impacted by the used colorimetry system and the relation between the involved displays' spectral power distributions (SPDs). In this work, we assess the metameric failure between the upcoming types of theatrical projectors, RGB laser, and laser phosphor (LaPH) and propose a method to reduce it. Our analysis starts by evaluating the performance of existing colorimetry systems in terms of metameric failure reduction. Among the colorimetry systems tested, the CIE 2006 2° (CIE06 2°) system resulted in the least observed metameric failure for a large portion of the participants but not their absolute majority (>50%). The limited performance of existing colorimetry systems led us to questioning the feasibility of successful perceptual color matching between the two projectors. To explore and potentially rule‐out this scenario, we performed a subjective color matching experiment. The analysis of the results revealed the key role that the projectors' SPD differences play on color matching. Based on the observations of the first two studies, we propose a novel colorimetry system that reduces further than existing colorimetry the systems the metameric failure between RGB and LaPH projectors. Our proposed system is a modified version of CIE06–2° that accounts for the spectral differences of the two light sources. Evaluation showed that our solution outperforms existing colorimetry systems. Abstract : The proposed colorimetry system is designed to reduce the metameric failure between RGB and laser phosphor projectors. The definition of the proposed system is based on two subjective studies where existing colorimetry systems are also evaluated.